PENGEMBANGAN ANALISIS BUTIR SOAL URAIAN BERBASIS ICT - Ilmi Fadhilah Marwa; Muhammad Kris Yuan Hidayatullah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to develop an application for analysis of item descriptions in desktop form to determine the feasibility of the Anabus Application based on the assessments of expert lecturers, expert teachers and teacher responses. This research is development research or (R&D) Research and Development which is adapted from the ADDIE development model. The development stage of the ADDIE model has 5 stages, including: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. Validation was carried out by expert lecturers, expert teachers, and tested on 30 respondents, namely 30 educators at Al-Hikmah Sumobito Middle School, Jombang. The results of this research show that the level of feasibility of the Anabus application is: 1) The first media expert obtained a total score of 56.00, which is included in the